FORGING CONNECTIONS ACROSS REMOTENESS: Colonization Projects and Global Dynamics in Amazonia and the Guianas (Late 1800s - Early 1900s) - BASÍLIO, ROMÁRIO SAMPAIO (Outros Tempos: Pesquisa em Foco - História, 2024)
This paper analyzes colonization projects and schemes that aimed to connect two remote regions in South America: the northern Brazilian Amazonia and the British colony of Guyana, during the transition from the late nineteenth century to the early twentieth century. The central problem is to understand projects designed to break or reduce remoteness and create cross-border connections (infrastructure, social and commercial linkages) that would cross societies and markets in different crisis scenarios, and to question the extent to which the ‘decadence’ denounced by contemporaries was a conjunctural element within long-term structural dependencies that cannot be solely attributed to competitiveness, mechanization limitations, or production rationalization. This study adopts a diachronic historical approach to examine three key aspects: (1) the challenges posed by the prolonged dominance of sugar monoculture in British Guyana and the concurrent rubber boom in the Brazilian Amazonia; (2) the interrelated matters of circulation and labor scarcity; and (3) the persistent issue of food shortages amid the setbacks encountered by integration endeavors.